2018
DOI: 10.1186/s12903-017-0470-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of risk-based payment model on caries inequalities in preschool children assessed by geo-mapping

Abstract: BackgroundTo describe, with aid of geo-mapping, the effects of a risk-based capitation model linked to caries-preventive guidelines on the polarization of caries in preschool children living in the Halland region of Sweden.MethodsThe new capitation model was implemented in 2013 in which more money was allocated to Public Dental Clinics surrounded by administrative parishes inhabited by children with increased caries risk, while a reduced capitation was allocated to those clinics with a low burden of high risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Geomapping, i.e. the geographical mapping of health data, has been described as a new tool to monitor health risk for medical as well as dental health purposes [22][23][24]. In Sweden, this tool has been used not only to illustrate the inequalities in caries risk among children living in Halland region in southwest Sweden but also to evaluate the effects of allocating more money to parishes inhabited by children with increased caries risk [23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…Geomapping, i.e. the geographical mapping of health data, has been described as a new tool to monitor health risk for medical as well as dental health purposes [22][23][24]. In Sweden, this tool has been used not only to illustrate the inequalities in caries risk among children living in Halland region in southwest Sweden but also to evaluate the effects of allocating more money to parishes inhabited by children with increased caries risk [23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…A study from Glasgow, Scotland, reported that investment in housing-led renewal according to population need leads to modest reductions in area-based health inequalities after 5 years [47]. Additionally, a risk-based capitation model reduced socio-economic inequalities in dental caries among preschool children living in Sweden [48]. These results suggest that proportionate universalism can be an effective strategy to reduce oral health inequalities, but more evidence is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Neighborhood-level sociodemographic data in Canada are available at the level of forward sortation area (FSA) postal codes [ 17 ], which have been used by both diabetes and cancer researchers as a measure of neighborhood-level socioeconomic status [ 18 , 19 ]. There is some data on the mapping of dental caries according to postal codes in children [ 20 ], and the relationship between dental billing data and neighborhood-level sociodemographic variables among Canadian children has recently been explored [ 21 ]. The present study examined whether the association of neighborhood-level socioeconomic status (SES) with the cost of dental care and dental care outcomes differs between adolescents and young adults.…”
Section: Introductionmentioning
confidence: 99%